A new paradigm for epidermal growth factor receptor expression exists in PTC and NIFTP regulated by microRNAs - Al-Abdallah, Abeer; Jahanbani, Iman; Ali, Rola H.; Al-Brahim, Nabeel; Prasanth, Jeena; Al-Shammary, Bashayer; Al-Bader, Maie (Frontiers in Oncology, 2023)
Abstract: Identification of molecular alterations associated with tumor behavior is necessary to guide clinical management. The 2022 WHO classification has organized the thyroid follicular cell-derived neoplasms into benign, low risk and high risk neoplasms, and emphasized the value of biomarkers that may provide differential diagnostic and prognostic information to avoid overtreatment of low risk neoplasms. This work aims to study the epidermal growth factor receptor (EGFR) expression, functional and spatial dynamics in relation to specific miRNAs alterations in papillary thyroid cancer (PTC) and in non-invasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) considered as models of high-risk and low-risk thyroid tumors respectively. Primary thyroid cultured cells were used for miRNA gain/loss of function and luciferase reporter assays. Paraffin embedded tissues were used for real time PCR, immuno-fluorescence stain and confocal microscopy experiments. Our results showed that in PTC, EGFR mRNA is reduced as an effect of miR-146b-5p upregulation. The EGF expression is low and the ERK pathway is inhibited. The EGFR protein high cytoplasmic expression and colocalization with the endosomal/exosomal markers, ALIX and CD63, suggest the occurrence of stress-induced EGFR internalization, accumulation in endosomal vesicles and secretion via exosomes. In NIFTP EGFR transcription is increased in association with downregulation of miR-7-5p and the EGFR/ERK pathway is active indicating dependence on the canonical EGFR pathway for growth. Downregulation of transcript level along with cytoplasmic accumulation of undegraded protein is a new pattern of EGFR regulation associated with malignancy in thyroid. Further research is needed to elucidate the intracellular trafficking defects responsible for this specific EGFR dynamic in PTC.